IMPLEMENTASI METODE TRIPLE EXPONENTIAL SMOOTHING DALAM MERAMALKAN PENERIMAAN CUKAI HASIL TEMBAKAU DI KPPBC TMP C BLITAR - Susi Darmawaningsih; Rizka Rizqi Robby (JURNAL DIFERENSIAL, 2022)
Forecasting is an important tool in effective and efficient planning. One of the time series methods in objective forecasting is the exponential smoothing method which is a procedure that continuously improves forecasting by averaging (smoothing = smoothing) the past value of a time series data in a decreasing way (exponential). The purpose of this research is to predict the amount tax receipt from tobacco at the Office of Supervision and Service of Customs and Excise Intermediate Customs Type C Blitar using the triple exponential smoothing method by finding the smallest error using MAD (Mean Absolute Deviation), MSE (Mean Square Error) and MAPE (Mean Absolute Percentage Error) which is tested with a constant value of . Excise on tobacco products is a state income that is managed through the mechanism of the state revenue and expenditure budget has a fairly important and strategic role in financing government programs and performance as well as development throughout the territory of the Unitary State of the Republic of Indonesia in a planned, orderly, safe, fair and sustainable manner, so that the prosperity and people's welfare. The implementation of mathematics to be applied to statistical data is very necessary especially to predict future state treasury receipts. For that in this research the Triple Exponential Smoothing method is used which uses a constant value of to . The results of this test produce the smallest error value with a constant value of α =0.1 with a MAPE result of 0,27%.